Electropolymerization of Limonene and Its Nanocomposites with ZnO and TiO2 to Protect Stainless Steel 304L Alloy from Corrosion in 3.5% NaCl Solution - Alqudsi , Ayat Monther; Saleh , khulood Abid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The surface disintegration of metals and alloys in a particular surrounding environment is known as corrosion, in addition to its chemical qualities, corrosion processes change the physical and mechanical properties of a metal alloy. A new approach based on a unique material has been employed to prevent rusting. Conducting polymer-composites are material types that show promise for anticorrosion by electrochemical synthesis of polylimonene/metals oxide nanocomposite (ZnO,TiO2) on Stainless Steel 304L, which plays as the working electrode by using the electropolymerization technique. The synthesized coating polymer was characterized by Fourier transform-infrared spectroscopy and atomic force microscopy checkups. The findings demonstrated that, when compared to the blank SS304L, PL/nanocomposite and PL provide the strongest corrosion defenses for the metal. The results explained that the corrosion protection increased from 52% for PL film to 89% for PL/ZnO film and to 97% for PL/TiO2 at 298K. In addition, calculations were made for the kinetic and thermodynamic parameters (Ea, A, ∆H, and ∆S). Escherichia coli and Staphylococcus aureus, two gram-positive and gram-negative bacteria, were used to test the biological activity of polymeric film (E.Coli).